ISOLASI DAN IDENTIFIKASI BAKTERI ASAM LAKTAT DARI LIUR BASA (LIMBAH SAYUR BAYAM DAN SAWI) - Sasmita Sasmita; Aliansyah Halim; Aisyah Nur Sapriati; Sukriani Kursia (As-Syifaa Jurnal Farmasi, 2018)
Lactic acid bacteria (BAL) is a gram-positive bacterium in the form of stems or round, not forming spores, anaerobic facultative fermentation and has the ability to ferment glucose into lactic acid. The purpose of this study was to isolate and identify lactic acid bacteria from spinach and mustard vegetable waste which can be used as food preservative. The isolation result was obtained by 10 isolates suspected as lactic acid bacteria. The isolates obtained were identified macroscopically, fermentation test, gram staining, spore staining and catalase test. From the macroscopic identification of samples of spinach and mustard, the isolates were white milk, rounded circular edges, kensitri surface and convex elevation. The fermentation test indicates that are heterofermentative and. All isolates obtained in the form of gram-positive bacteria had no negative spores and catalases and its alleged are Lactobasillus.